Genome engineering for crop improvement - Upadhyay, Santosh Kumar (Hoboken, New Jersey : Wiley, 2021)
'Genome engineering tools like ZFNs, TALENs and CRISPR-Cas system have been extensively studied in various crop plants. In the last decades, they have been utilized in numerous agricultural and horticultural crop plants including rice, wheat, legumes, tomato, potato, banana, grapes etc. They are found to be highly specific and precise in functioning. They have been used for the engineering of numerous metabolic pathways to develop nutrient rich produce. They are also being utilize to decrease the anti-nutrients in crop plants to improve the bioavailability of minerals and vitamins, development of zero calorie/ sugar free potato, undigestable starch rich grains, allergenic gluten free wheat and various other processes. Further they can also be utilized for the mobilization of minerals from unavailable location to the bioavailable location in the grains. Development of new strategies to cope up with the various challenges has always been a top priority in recent years. Agronomical practices, chemical applications, biofortifications and transgenic expression of protein coding genes have been explored to alleviate these problems to some extent. However, new and specific technology is always in demand. The genome engineering tools can be a best alternative for nutritional improvement of agricultural and horticultural crops. Further, it will be highly specific to a particular gene and plant'--
Includes bibliographical references and index.
Keywords: Crops -- Genetic engineering; Plant biotechnology